The story of George Washington - Pingry, Patricia A., 1941-; Britt, Stephanie (Nashville, Tenn. : CandyCane Press, 2000)
Presents a simple introduction to the life of George Washington, from his birth to his retirement from service to the newly formed United States.
On board pages.
2.3
K-3
K-3
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Washington, George, -- 1732-1799.; Presidents; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography